PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI BADAN PENGAWAS OBAT DAN MAKANAN DI BATAM - Saiful, A. Saiful Rosiin; Asron, Asron Saputra, S.E., M.Si (SCIENTIA JOURNAL, 2022)
The purpose of this study was to determine the effect of motivation and job satisfaction on the performance of the Food and Drug Supervisory Agency employees in Batam, using a saturated sample of 106 respondents. The method used in collecting data in this study used questionnaire data. The data quality test uses validity and reliability tests, classical assumption tests and influence tests in this study using multiple linear regression analysis and analysis of the coefficient of determination, while in hypothesis testing this study uses t test and f test with the help of SPSS version 25 program. R square test got a score of 51% which states that there is an influence of motivation and job satisfaction on employee performance and the remaining 49% is influenced by other variables outside this study. The results of the multiple linear regression test prove that motivation affects performance with a score of 22% and job satisfaction affects performance with a score of 43.6%. Based on the results of the t-test and f-test, it can be concluded that motivation and job satisfaction have a partially significant effect on employee performance, and motivation and job satisfaction simultaneously have a significant effect on the performance of the Food and Drug Supervisory Agency employees in Batam.